2011
DOI: 10.1080/0013791x.2011.573615
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Function for the Natural Gas Transmission Industry: Further Considerations

Abstract: This article studies the cost function for the natural gas transmission industry. In addition to a tribute to H.B. Chenery, it firstly offers some further comments on a recent contribution (Yépez, 2008): a statistical characterization of long-run scale economies, and a simple reformulation of the long-run problem. An extension is then proposed to analyze how the presence of seasonally-varying flows modifies the optimal design of a transmission infrastructure. Lastly, the case of a firm that anticipates a possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Firstly, the elasticity of the long-run cost with respect to output is 9 11 β = and lower than one. The cost function (5) also validates the empirical remarks in Chenery (1952) and Massol (2011) who suggested that this elasticity is almost constant over most of the output range. Secondly, the ratio of the long-run marginal cost to the long-run average cost is constant and also equals β .…”
Section: Long-run Costsupporting
confidence: 77%
See 1 more Smart Citation
“…Firstly, the elasticity of the long-run cost with respect to output is 9 11 β = and lower than one. The cost function (5) also validates the empirical remarks in Chenery (1952) and Massol (2011) who suggested that this elasticity is almost constant over most of the output range. Secondly, the ratio of the long-run marginal cost to the long-run average cost is constant and also equals β .…”
Section: Long-run Costsupporting
confidence: 77%
“…Yet, because of its sophistication and its numerical nature, it is seldom considered in regulatory policy debates (Massol, 2011). The second approach involves the econometric estimation of a flexible functional form -usually a translog specification -to obtain an approximate cost function.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Interconnector operator, the nominal transportation capacity from the UK to pipeline is a time-varying parameter that depends on a series of exogenous factors (e.g., the operating pressures of the adjacent national pipeline systems, the flow temperature, the chemical composition of the natural gas (Yépez, 2008;Massol, 2011). Hence, the historical maximum daily flow cannot necessarily be attained.…”
Section: Datamentioning
confidence: 99%
“…These cost simulations consistently indicate that the technology at hand exhibits very marked increasing returns to scale over a large range of output in the long run (IPCC, 2005;McCoy and Rubin, 2008;McCoy, 2009 (André and Bonnans, 2011;Massol, 2011), and (ii) the numerous applications of mathematical programming to model meshed networks (e.g., De Wolf and Smeers, 1996;André et al, 2009). 6 There exists some technological differences between natural gas and CO 2 pipelines systems as methane is typically piped in a gaseous state whereas CO 2 is piped in supercritical state (McCoy and Rubin, 2008).…”
Section: Economies Of Scale In Co 2 Pipeline Systemsmentioning
confidence: 90%